Design a Magnetic Bearing Control System to Reduce the Deflection of Rotating Shafts - أنس السلومي; هيثم وردة; موفق منجد (Latakia University Journal -Engineering Sciences Series, 2024)
Magnetic bearings are based on the principle of using a magnetic field to lift rotating shafts and therefore do not contain any friction or wear, which gives them high reliability in addition to speed that is not possible to achieve with other bearings, which can be easily achieved using these bearings. The use of these bearings in rotating machines also reduces vibration in the machine, which improves the life of the machine and thus increases its periodic maintenance periods.. The design of the control system for such bearings is considered the main point in the quality of the work of these bearings, as the control system works to read the deviation in the rotating axis within the bearing and adjusts it by adjusting the intensity of the current passing through its coils, which changes the intensity of the generated magnetic field and thus returns the axis to its position. What we have done in this research is to design a traditional and advanced control system for a mathematical model of a rotating axis supported by a magnetic bearing using the MATLAB/SIMULINK program to reduce the deviation of the rotating axis within the bearing in order to reduce wear and tear in traditional bearings and increase the speed of rotation of these axes in machines, as the results showed. The use of an advanced control system for the magnetic bearing led to a greater reduction in axis deviations than the traditional control system.